Improving Environmental Literacy Through the Utilization of Ecobrick Media for Second Grade Students at Tanjungrejo 4 Public Elementary School - Niken Ardhinata; Nury Yuniasih; Ernawati Ernawati (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2026)
Abstract: This study aimed to improve the environmental literacy of second-grade students through the utilization of ecobrick media integrated with the Project Based Learning (PjBL) model at SD Negeri Tanjungrejo 4 in Malang City. The study was motivated by students’ low understanding and implementation of environmental literacy, as reflected in habits such as littering, poor classroom cleanliness, and limited awareness of the surrounding environment. This research employed Classroom Action Research conducted in two cycles involving 23 students during the 2025/2026 academic year. Each cycle included planning, action implementation, observation, reflection, and evaluation stages. Data were collected through a pretest, Cycle I posttest, and Cycle II posttest measuring cognitive, affective, and behavioral indicators of environmental literacy. The findings showed a significant improvement in students’ learning outcomes. The average pretest score increased from 36.22 to 64.78 in Cycle I and reached 84.74 in Cycle II. Learning mastery improved from 30.43% in the pretest to 73.91% in Cycle I and 91.30% in Cycle II. The n-gain analysis indicated that most students achieved a high category in Cycle II, demonstrating the effectiveness of the PjBL ecobrick project. Keywords: Environmental literacy, Ecobrick, Project Based Learning, Classroom Action Research, Elementary school.